2001
DOI: 10.1038/83567
|View full text |Cite
|
Sign up to set email alerts
|

A helper phage to improve single-chain antibody presentation in phage display

Abstract: We show here that the number of single-chain antibody fragments (scFv) presented on filamentous phage particles generated with antibody display phagemids can be increased by more than two orders of magnitude by using a newly developed helper phage (hyperphage). Hyperphage have a wild-type pIII phenotype and are therefore able to infect F(+) Escherichia coli cells with high efficiency; however, their lack of a functional pIII gene means that the phagemid-encoded pIII-antibody fusion is the sole source of pIII i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 264 publications
(219 citation statements)
references
References 22 publications
4
215
0
Order By: Relevance
“…Although unnatural amino acids have been displayed on WT M13 phage in single peptides (14), such a system was not amenable to directed evolution experiments within these constraints. We therefore turned to phagemid display, specifically multivalent hyperphage phagemid display (15,16), which we felt would fulfill these two criteria for both the canonical and unnatural amino acids.…”
Section: Proteins Containing Unnatural Amino Acids Are Correctly Dispmentioning
confidence: 99%
“…Although unnatural amino acids have been displayed on WT M13 phage in single peptides (14), such a system was not amenable to directed evolution experiments within these constraints. We therefore turned to phagemid display, specifically multivalent hyperphage phagemid display (15,16), which we felt would fulfill these two criteria for both the canonical and unnatural amino acids.…”
Section: Proteins Containing Unnatural Amino Acids Are Correctly Dispmentioning
confidence: 99%
“…First, repeat series of biopanning can be performed (Edwards et al, 2003). Second, antibody fragments can be displayed with increased efficiency on virions Rondot et al, 2001). Third, increased numbers of biopanned clones can be tested by robotic high throughput screening (de Wildt et al, 2000;Konthur et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…11 These same authors found that strains lacking WaaL (e.g., E. coli CLM24) exhibited more efficient N-glycosylation of a native C. jejuni glycoprotein by PglB. Another improvement would be to utilize helper phage that lack a copy of the native g3p protein, so-called hyperphage, 32 thereby permitting more efficient incorporation of the engineered MBP DQNAT -g3p fusion into phage particles. Alternatively, the ''helperless'' phage system developed by Bradbury and coworkers could offer a similar improvement.…”
Section: Discussionmentioning
confidence: 99%